Implications of The Universal Human Nasr In the formulation of Islamic Educational Goal - Bima Azisza Mahardika; Mohamad Ali (Universitas Muhammadiyah Surakarta, 2018)
Seyyed Hossein Nasr views the development of the modern Western world critically. According to him, modern humans have alienated humans from the values of spirituality that cause humans to forget their existence on earth. Understanding human nature is very important to do when it is associated with education. Education must have a goal so that it has the direction to be achieved in an educational process. This study aims to understand the meaning of human beings according to Nasr and their implications in the formulation of the goal of Islamic education. This type of research is library research with a philosophical approach. Researchers managed to find a universal human being is a human who is able to understand the nature of himself, realizing he is a reflection of the nature and name of God. Universal human always carry out the responsibility given by God to him, managing the potential that exists in themselves to support the fulfillment of responsibility towards God. The implication of Nasr's universal human concept in the formulation of educational goals is that universal human learners (insan al-kamil). Islamic students who are able to utilize the potential of their intellect to help carry out responsibility to God.